Diagnosing Factors behind Officers’ Performance in the Philippine National Police - Mendoza, Ronald U (Archīum Ateneo, 2020)
The Philippine National Police (PNP) faces myriad challenges, spanning governance, corruption and national security threats. Hence, securing a strong leadership pipeline equipped not only to face these challenges, but also to strengthen policing effectiveness and over-all security sector reforms is crucial. This study aims to map out some of the main factors that both build or erode key leadership qualities and performance in the PNP. Using quantitative and qualitative methods, the study examines four main factors, namely personality traits, organizational culture, demographic profile and professional history, as predictor of performance for officers in the National Capital Region. It finds evidence that personality traits, specifically openness, agreeableness and neuroticism, as well as number of transfers, area of assignment, training on managerial skills, age and education level are all factors for good performance for officers in the PNP National Capital Region Police Office. These results emphasize the importance of training and mentoring components in preparing young officers and recruits for the rigors of service. It also underscores the need for a deeper analysis of recruitment and selection policies, to ensure that the PNP successfully attracts the strongest candidates with the right leadership characteristics and building blocks for service.